Activated Carbon‐Supported Mo‐Co‐K Sulfide Catalysts for Synthesizing Higher Alcohols from CO2. Issue 5 (27th February 2019) - Liu, Su; Zhou, Haibo; Zhang, Lin; Ma, Zhen; Wang, Yangdong
Abstract: Activated carbon‐supported Mo‐Co‐K sulfide catalysts, prepared by stepwise impregnation, were used in the synthesis of higher alcohols via CO2 hydrogenation. The catalysts with varying Mo contents and defined K/Mo and Co/Mo molar ratios exhibited relatively high CO2 conversions and high selectivity to total alcohols and C2+ alcohols. Moreover, the influence of calcination conditions on the sulfidation states and catalytic performance was studied. The surface sulfur runoff of the supported catalysts can be effectively suppressed by online calcination. As a result, the selectivity to total alcohols and C2+ alcohols can be improved. Abstract : Activated carbon‐supported Mo‐Co‐K sulfide catalysts were prepared by stepwise impregnation in a more economical and environmentally friendly way compared to the bulk‐phase MoS2 ‐based catalyst and applied for the synthesis of higher alcohols via CO2 hydrogenation. Optimization of the Mo loading content, Co/Mo and K/Mo molar ratios further improved the performance of the catalysts.